1979
DOI: 10.1063/1.437583
|View full text |Cite
|
Sign up to set email alerts
|

Rotational motions of NH+4 groups in NH4ZnF3 studied by quasielastic neutron scattering

Abstract: The rotational behavior of the ammonium groups in the high-temperature cubic phase of the perovskite NH4ZnF3 has been investigated, using incoherent quasielastic neutron scattering. The measurements were carried out for various wave vector transfers between 0.68 and 5.52 Å−1 and for temperatures between the transition temperature of 115.1 and 300 K. The data are compared with some reorientational jump models. It is assumed that in the cubic phase the NH4 group is a slightly distorted tetrahedron, apparently du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

1981
1981
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(1 citation statement)
references
References 9 publications
0
0
1
Order By: Relevance
“…The activation temperature EJkB = 650 K that we have found for NH4ZnF3 above 115K is somewhat higher than the 585 f 15K that Steenbergen et al [26] have found from neutron scattering. Burriel [27, quoted in 171 has attempted to calculate the electrostatic barriers in NH4ZnF3 and NH4MnF3 but his results of order 2000K are clearly too large.…”
Section: Discussioncontrasting
confidence: 69%
“…The activation temperature EJkB = 650 K that we have found for NH4ZnF3 above 115K is somewhat higher than the 585 f 15K that Steenbergen et al [26] have found from neutron scattering. Burriel [27, quoted in 171 has attempted to calculate the electrostatic barriers in NH4ZnF3 and NH4MnF3 but his results of order 2000K are clearly too large.…”
Section: Discussioncontrasting
confidence: 69%